Mobile TV: where we are and where we are going - Bartley Boston (International Journal of Science and Society, 2022)
The article presents (1) the technical characteristics of Mobile TV [Mobile TV] and how it differs from IPTV and Internet TV [Internet TV], (2) network, spectrum and equipment issues that will influence the regulatory framework, (3) the opportunities created for Mobile TV when migrating to digital TV, and (4) a case study in Mexico concerning the regulatory framework for telecommunications and broadcasting services, market players, spectrum availability, migration to digital TV and other issues prominent for Mobile TV